H-Block : the British government's treatment of Irish political prisoners. (Belfast New York : H-Block Information Centre Irish Northern Aid, 1978)
Bibliotheek François Vercammen
D/82/008/DOC
Engels
Monografie
Keywords: politieke gevangenen; Noord-Ierland.